Disease pattern and Biochemical profile as a predictor of outcome of Critically sick neonates in a Neonatal Intensive Care Unit - Yusuf, Mir Mohammad; Yasmeen, BH Nazma; Chowdhury, MAK Azad (Northern International Medical College Journal, 2020)
Background: Neonatal Intensive Care Unit (NICU) is predominately concerned with the management of critically sick neonates having acute life threatening conditions. Usually neonates having respiratory distress, acute neurological deterioration, severe infection and prematurity contribute the major admission in a NICU. Objective: To find out the disease pattern and biochemical profile as a predictor of outcome of critically sick neonates in NICU. Methods: This observational prospective study was carried out at NICU of Dhaka Shishu (Children) Hospital from January 2015 to July 2015. Total 121 neonates were enrolled according to inclusion criteria and analyzed some important biochemical profile specially electrolyte and blood gas status as a part of proper management as well as to predict their outcome. Results: Among critically sick neonates, perinatal asphyxia was common disorder followed by sepsis. Biochemical profile specially electrolyte and acid-base disruption play important role to the outcome of critically sick neonates. Low pH, low potassium and high base-deficit level were found to have worse outcome. Conclusion: Perinatal asphyxia constitutemajor cause of admission ofcritically sick neonates. Early detection of electrolyte and acid-base status is helpful to care and overall survival of these neonates. Mortality was the highest among neonatal sepsis followedby perinatal asphyxia. Metabolic acidosis and hypokalemia were the predictor of outcome of such critically sick neonates. Northern International Medical College Journal Vol.10 (2) Jan 2019: 381-385